Using the PRECEDE Planning Approach to Develop a Physical Activity Intervention for African American Men Who Visit Barbershops: Results From the FITShop Study. (July 2015) - Hood, Sula; Linnan, Laura; Jolly, David; Muqueeth, Sadiya; Hall, Marla B.; Dixon, Carrissa; Robinson, Seronda
African American (AA) men have a higher prevalence of many chronic disease risk behaviors compared to Caucasian men, including physical inactivity. Innovative ways to reach AA men with interventions to increase physical activity (PA) and decrease other key risk factors are needed to reduce health disparities in this population. The barbershop is a natural but underutilized setting for reaching AA men. In the Fitness in the Shop (FITShop) study, shop owners, barbers, and customers were recruited from four local barbershops to complete structured interviews and customer focus groups. We assessed knowledge, perceived barriers, and interests/concerns about PA, as well as explored how to best intervene in the barbershop. Barbers and customers endorsed the idea of receiving health and PA information in the barbershop. These formative research results generated information and strategies for developing a multilevel barbershop-based health intervention to promote PA in the barbershop. This article describes the formative research results and how PRECEDE was used to develop a culturally and contextually appropriate, multilevel barbershop-based intervention designed to promote PA and to reduce chronic disease disparities among AA men.